Housing property investment opportunity in Malaysia: things that new investor should know - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2022)
This paper aimed to review things that new investors should know in Malaysia housing property investment. Housing property prices tend to rise over time, so a house is one of the best investments. However, don’t be influenced by people telling you that since prices have dropped now, it is a great time to buy a house. There are several perspectives viewed in this review such as how properties can make money for the investor, things that need to be considered in selecting a property for investment and the risk in property investing. All information is gathered from previous research articles and property news, feedback and discussion from properties and real estate websites. There are tons of information shared by “PropertyGuru” on the website which uses as guidance for the investor. There is a big opportunity for the investor to invest in housing property in Malaysia, as housing property development in Malaysia growing very well over the years. This paper could clear some of the concerns and aid the new investor in their investments. This paper begins with a review of housing property investment in Malaysia, making money from the properties, and the consideration in selecting a property for investment. Next, this paper discusses the risk in property investment.